Implementasi Hukum Syariah dalam Sistem Ekonomi Islam di Indonesia: Tantangan dan Peluang - Jaya Mahendra; Bima Saputra Pradana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article discusses the implementation of sharia law in the Islamic economic system in Indonesia, focusing on the challenges and opportunities faced. This research uses the method of literature study and interviews with Islamic economic practitioners. The results show that although the regulation of Islamic economics is growing, there are still challenges in terms of public understanding, limited competent human resources, and competition with conventional economic systems. Therefore, a more effective strategy is needed in improving Islamic economic literacy, strengthening regulations, and developing Islamic financial institutions in order to contribute more to the national economy.